Linguistic problems of translation of Arabic terms into Russian (Journal of Oriental Studies, 2016)
In the Arabic language there are some linguistic and extra linguistic problems of translation of terminological units. In this paper we examine whichthe linguistic problems are presented in the translation process of the Arabic terms into Russian.